A glimpse of gluons through deeply virtual compton scattering on the proton. Issue 1 (December 2017) - Defurne, M.; Jiménez-Argüello, A. Martí; Ahmed, Z.; Albataineh, H.; Allada, K.; Aniol, K.; Bellini, V.; Benali, M.; Boeglin, W.; Bertin, P.; Brossard, M.; Camsonne, A.; et al.
Abstract The internal structure of nucleons (protons and neutrons) remains one of the greatest outstanding problems in modern nuclear physics. By scattering high-energy electrons off a proton we are able to resolve its fundamental constituents and probe their momenta and positions. Here we investigate the dynamics of quarks and gluons inside nucleons using deeply virtual Compton scattering (DVCS)—a highly virtual photon scatters off the proton, which subsequently radiates a photon. DVCS interferes with the Bethe-Heitler (BH) process, where the photon is emitted by the electron rather than the proton. We report herein the full determination of the BH-DVCS interference by exploiting the distinct energy dependences of the DVCS and BH amplitudes. In the regime where the scattering is expected to occur off a single quark, measurements show an intriguing sensitivity to gluons, the carriers of the strong interaction. It remains a challenge to find the structure and the distribution of the constituents of nucleons. Here the authors use a scattering method to get information about the gluons and quarks inside a proton and separate the contribution of Bethe-Heitler from the deeply virtual Compton scattering process.